2001
DOI: 10.1002/1096-9896(200109)195:1<20::aid-path933>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The immune system and gene expression microarrays - new answers to old questions

Abstract: The recent increase in availability of gene expression technologies has the potential to dramatically expand our understanding of cellular immunology in molecular detail. Expression levels of tens of thousands of genes can be measured in dozens of samples in only a few days, and this data can be integrated with sequence informatics to tentatively assign some (limited) functional information to a majority of these genes. In this review we discuss some initial applications of these new tools to the fields of lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 93 publications
(95 reference statements)
1
15
0
Order By: Relevance
“…In contrast, AML cells with monocytic differentiation (FAB-M4/M5) showed altered expression of genes mainly involved in intracellular signal transduction and regulation of DNA-repair, cell cycle events or DNA transcription (Supplementary Table II). This last observation is consistent with reports regarding essential regulation of gene expression during monocyte differentiation (38,39). Previous studies have reported that unsupervised cluster analysis sorted AML samples according to cytogenetic abnormalities rather than FAB phenotypes (12) and that gene expression correlates with the common AML translocations [t(8;21), t(15;17), inv (16)], and translocations involving 11q23 have also been described (12,(40)(41)(42).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, AML cells with monocytic differentiation (FAB-M4/M5) showed altered expression of genes mainly involved in intracellular signal transduction and regulation of DNA-repair, cell cycle events or DNA transcription (Supplementary Table II). This last observation is consistent with reports regarding essential regulation of gene expression during monocyte differentiation (38,39). Previous studies have reported that unsupervised cluster analysis sorted AML samples according to cytogenetic abnormalities rather than FAB phenotypes (12) and that gene expression correlates with the common AML translocations [t(8;21), t(15;17), inv (16)], and translocations involving 11q23 have also been described (12,(40)(41)(42).…”
Section: Discussionsupporting
confidence: 90%
“…Other studies, involving genomic-scale approaches to evaluate immune responses against viral infections, have used mostly cDNA microarrays (11,16,18,34,46,54). The method used here, which combined subtracted cDNA libraries and DNA macroarrays, is simple, practical, and less expensive than microarrays.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of success using this technology include the search for genes specifically expressed in diseases like cancer [25][26][27][28], viral infection [29], inflammation [30][31][32] or hematopoietic disorders [33], and the examination of genes specifically expressed in certain lineages of differentiated cells. However, we have experienced some difficulties in applying this technology.…”
Section: Discussionmentioning
confidence: 99%